2012
DOI: 10.1016/j.matlet.2012.05.130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing on the structural, topographical and optical properties of sol–gel derived ZnO and AZO thin films

Abstract: A comparative study of the physical properties of undoped Zinc Oxide (ZnO) and Al doped Zinc Oxide (AZO) thin films were performed as a function of annealing temperature. The structural properties were analyzed using X-ray diffraction and the recorded patterns indicated that the crystallinity of the films always enhanced with increasing annealing temperature while it degrades with Al doping. The topographical modification of the films due to heat treatment was examined by atomic force microscopy which revealed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 10 publications
2
33
1
2
Order By: Relevance
“…6, the UV emissions peak of undoped sample is at 3.297 eV, while that of Al-doped sample is 3.324 eV. Compared with the undoped ZnO nanowire arrays, the PL spectra of the doped ZnO nanowires arrays exhibited an obvious blue-shift in the UV emission, which is attributed to be a result of the BursteineMoss effect because of the Al doping [32], confirms the presence of Al doping in ZnO nanowire arrays. Moreover, the weaker green emission of AleZnO nanowires arrays illustrates that the AleZnO nanowire arrays have higher crystalline quality and fewer defects, as well as lower surface states.…”
Section: Resultsmentioning
confidence: 60%
“…6, the UV emissions peak of undoped sample is at 3.297 eV, while that of Al-doped sample is 3.324 eV. Compared with the undoped ZnO nanowire arrays, the PL spectra of the doped ZnO nanowires arrays exhibited an obvious blue-shift in the UV emission, which is attributed to be a result of the BursteineMoss effect because of the Al doping [32], confirms the presence of Al doping in ZnO nanowire arrays. Moreover, the weaker green emission of AleZnO nanowires arrays illustrates that the AleZnO nanowire arrays have higher crystalline quality and fewer defects, as well as lower surface states.…”
Section: Resultsmentioning
confidence: 60%
“…ions precipitation form in ZnO. (Sengupta et al 2012) also reported that the shift of diffraction from (002) to (001) and (101) planes was due to increased concentration of 'Al' in 'ZnO' beyond the solubility limit.…”
Section: Resultsmentioning
confidence: 93%
“…After the Cd ion incorporation, it was found from PL spectra that the peak of NBE emission of Cd-doped ZnO film, in comparison to undoped ZnO, blue shifted to the higher energy side. This blue-shift in the UV emission is believed to be a result of the Burstein-Moss effect because of the doping [21]. In our system, the Cd-doped ZnO sample revealed n-type with a carrier density of 1.29 Â 10 18 cm À 3 (a resistivity of 0.28 Ω cm and a mobility of 20 cm 2 /V s), in comparison to undoped ZnO with a carrier density of 5.55 Â 10 17 cm À 3 (a resistivity of 0.14 Ω cm and a mobility of 8 cm 2 /V s), with more free electrons contributed by Cd dopant would take up the energy levels located at the bottom of the conduction band.…”
Section: Resultsmentioning
confidence: 98%